CD44 deletion leading to attenuation of experimental autoimmune encephalomyelitis results from alterations in gut microbiome in mice. Issue 7 (6th June 2017) - Chitrala, Kumaraswamy Naidu; Guan, Hongbing; Singh, Narendra P.; Busbee, Brandon; Gandy, Alexa; Mehrpouya‐Bahrami, Pegah; Ganewatta, Mitra S.; Tang, Chuanbing; Chatterjee, Saurabh; Nagarkatti, Prakash; Nagarkatti, Mitzi
Abstract : CD44 deletion triggers attenuation of experimental autoimmune encephalomyelitis alteration of gut microbiome, increasing species belonging to Bacteroidetes changes in short chain fatty acid profile, increasing propionic and i‐buytric acid Abstract : Dysbiosis in gut microbiome has been shown to be associated with inflammatory and autoimmune diseases. Previous studies from our laboratory demonstrated the pivotal role played by CD44 in the regulation of EAE, a murine model of multiple sclerosis. In the current study, we determined whether these effects resulted from an alteration in gut microbiota and the short‐chain fatty acid (SCFA) production in CD44 knockout (CD44KO) mice. Fecal transfer from naïve CD44KO but not C57BL/6 wild type (CD44WT) mice, into EAE‐induced CD44WT mice, led to significant amelioration of EAE. High‐throughput bacterial 16S rRNA gene sequencing, followed by clustering sequences into operational taxonomic units (OTUs) and biochemical analysis, revealed that EAE‐induced CD44KO mice showed significant diversity, richness, and evenness when compared to EAE‐induced CD44WT mice at the phylum level, with dominant Bacteroidetes (68.5%) and low Firmicutes (26.8%). Further, data showed a significant change in the abundance of SCFAs, propionic acid, and i‐butyric acid in EAE‐CD44KO compared to EAE‐CD44WT mice. In conclusion, our results demonstrate that the attenuation of EAE seen following CD44 gene deletion in mice may result from alterations in the gut microbiota and SCFAs. Furthermore, our studies also demonstrate that the phenotype of gene knock‐out animals may be shaped by gut microbiota.